ANALISIS RESEPSI PENONTON TERHADAP KESENJANGAN KASTA DALAM FILM "THE WHITE TIGER" KARYA RAHMIN BRAHMANI - Sri Qania Dian Heriputrianti (2013)
This study aims to discuss the audience's reception of The White Tiger film regarding the caste gap contained in the film using Stuart Hall's Encoding Decoding Reception theory. Researchers focused on the variety of backgrounds that the informants had, one of which was religious differences. The method used in this research is descriptive qualitative with reception analysis approach. The researcher conducted interviews with informants who had different religious backgrounds to obtain data regarding the reception of the caste gap depicted in the film The White Tiger. Resource persons can be categorized into three reception positions, namely the Dominant position, the Negotiation position, and the Opposition position. The results of this study show that two of the four informants, namely Muslim and Protestant informants, are in a dominant position. This shows that the two informants interpret the caste gap in accordance with what is expected by the film producers. Both of them believe that the caste system that applies in India causes injustice in the socio-economic life of society. Two other informants namely Catholic and Hindu informants are in a Negotiation position. Both of them do not fully agree and have their own opinion in interpreting the caste gap. They argue that caste does not fully cause the deterioration of the socio-economic life of low-caste people. In addition, Hindu informants also argued that the caste system was no longer relevant to the modern life of today's society, so there was no need for criticism of the caste system. The informants disagreed as audiences because they had different imaginations from film producers and were motivated by different experiences and religions so that each of them had their own point of view in interpreting the caste gap in The White Tiger film.